Review of Post-Combustion Carbon Capture in Europe: Current Technologies and Future Strategies for Largest CO2-Emitting Industries - Luísa Marques; Miguel Monteiro; Charles Cenci; Maria Mateus; José Condeço (Energies)
Heavy industry is a significant contributor to CO2 global emissions, accounting for approximately 25% of the total. In Europe, the continent’s largest emitting industries, including steel, cement, and power generation, face significant decarbonization challenges due to multiple interrelated factors. Heavy industry must achieve carbon neutrality by 2050, as outlined in the 13th United Nations Sustainable Goals. One strategy to achieve this goal involves Carbon Capture Utilization and Storage (CCUS) with post-combustion carbon capture (PCC) technologies playing a critical role. Key methods include absorption, which uses chemical solvents like amines; adsorption, employing solid sorbents; cyclic CO2 capture, such as calcium looping methods; cryogenic separation, which involves chilling flue gas to liquefy CO2; and membrane separation, leveraging polymeric materials. Each technology offers unique advantages and challenges, necessitating hybrid approaches and policy support for widespread adoption. In this sense, this review provides a comprehensive overview of the existing European pilot and demonstration units and projects, funded by the EU across several industries. It specifically focuses on PCC. This study examines 111 industrial facilities across Europe, documenting the PCC technologies deployed at plants of varying capacities, geographic locations, and operational stakeholders. The review further evaluates the techno-economic performance of these systems, assessing their potential to advance carbon neutrality in heavy industries.